The role of cardiac troponin T quantity and function in cardiac development and dilated cardiomyopathy. - Ferhaan Ahmad; Sanjay K Banerjee; Michele L Lage; Xueyin N Huang; Stephen H Smith; Samir Saba; Jennifer Rager; David A Conner; Andrzej M Janczewski; Kimimasa Tobita; Joseph P Tinney; Ivan P Moskowitz; et al. (PLoS ONE, 2008)
Hypertrophic (HCM) and dilated (DCM) cardiomyopathies result from sarcomeric protein mutations, including cardiac troponin T (cTnT, TNNT2). We determined whether TNNT2 mutations cause cardiomyopathies by altering cTnT function or quantity; whether the severity of DCM is related to the ratio of mutant to wildtype cTnT; whether Ca(2+) desensitization occurs in DCM; and whether absence of cTnT impairs early embryonic cardiogenesis.We ablated Tnnt2 to produce heterozygous Tnnt2(+/-) mice, and crossbreeding produced homozygous null Tnnt2(-/-) embryos. We also generated transgenic mice overexpressing wildtype (TG(WT)) or DCM mutant (TG(K210Delta)) Tnnt2. Crossbreeding produced mice lacking one allele of Tnnt2, but carrying wildtype (Tnnt2(+/-)/TG(WT)) or mutant (Tnnt2(+/-)/TG(K210Delta)) transgenes. Tnnt2(+/-) mice relative to wildtype had significantly reduced transcript (0.82+/-0.06[SD] vs. 1.00+/-0.12 arbitrary units; p = 0.025), but not protein (1.01+/-0.20 vs. 1.00+/-0.13 arbitrary units; p = 0.44). Tnnt2(+/-) mice had normal hearts (histology, mass, left ventricular end diastolic diameter [LVEDD], fractional shortening [FS]). Moreover, whereas Tnnt2(+/-)/TG(K210Delta) mice had severe DCM, TG(K210Delta) mice had only mild DCM (FS 18+/-4 vs. 29+/-7%; p<0.01). The difference in severity of DCM may be attributable to a greater ratio of mutant to wildtype Tnnt2 transcript in Tnnt2(+/-)/TG(K210Delta) relative to TG(K210Delta) mice (2.42+/-0.08, p = 0.03). Tnnt2(+/-)/TG(K210Delta) muscle showed Ca(2+) desensitization (pCa(50) = 5.34+/-0.08 vs. 5.58+/-0.03 at sarcomere length 1.9 microm, p<0.01), but no difference in maximum force generation. Day 9.5 Tnnt2(-/-) embryos had normally looped hearts, but thin ventricular walls, large pericardial effusions, noncontractile hearts, and severely disorganized sarcomeres.Absence of one Tnnt2 allele leads to a mild deficit in transcript but not protein, leading to a normal cardiac phenotype. DCM results from abnormal function of a mutant protein, which is associated with myocyte Ca(2+) desensitization. The severity of DCM depends on the ratio of mutant to wildtype Tnnt2 transcript. cTnT is essential for sarcomere formation, but normal embryonic heart looping occurs without contractile activity.